Never let you go [compact disc, unabridged] - Stevens, Chevy (Blackstone Audio, 2017)
Eleven years ago, Lindsey Nash escaped into the night with her young daughter and left an abusive relationship. Her ex-husband, Andrew, was sent to jail and Lindsey started over with a new life. Now, Lindsey is older and wiser, with her own business and a teenage daughter who needs her more than ever. When Andrew is finally released from prison, Lindsey believes she has cut all ties and left the past behind her. But she gets the sense that someone is watching her, tracking her every move. Her new boyfriend is threatened. Her home is invaded, and her daughter is shadowed. Lindsey is convinced it's her ex-husband, even though he claims he's a different person. But has he really changed? Is the one who wants her dead closer to home than she thought? With Never Let You Go, Chevy Stevens delivers a chilling, twisting thriller that crackles with suspense as it explores the darkest heart of love and obsession.